Influence of the Retinal Methyl Groups on Retinal Structure and Dynamics - Sugihara, Minoru; Bondar, Ana-Nicoleta (Current Physical Chemistry, 2013)
The light-induced isomerization of the retinal chromophore starts the reaction cycles of retinal proteins. We review and discuss some new computations on the role of the retinal methyl groups in determining the structure, dynamics, and protein interactions of the retinal. The torsional potential of the C11=C12 bond suggests that moderate twisting of this bond can be achieved without a significant energetic cost, allowing for twisted 11-cis geometries to be sampled within the protein environment. The 9- and 13-methyl groups contribute significantly to the geometry and the ground-state torsional properties of the retinal chromophore, but the relative importance of these two methyl groups appears to be different in the dark- vs. the batho-intermediates of visual rhodopsins.
Keywords: Methyl groups